2019
DOI: 10.1097/md.0000000000018509
|View full text |Cite
|
Sign up to set email alerts
|

Two-years of home based functional electrical stimulation recovers epidermis from atrophy and flattening after years of complete Conus-Cauda Syndrome

Abstract: To evaluate progression of skin atrophy during 8 years of complete Conus-Cauda Syndrome and its recovery after 2 years of surface Functional Electrical Stimulation a cohort study was organized and implemented.Functional assessments, tissue biopsies, and follow-up were performed at the Wilhelminenspital, Vienna, Austria; skin histology and immunohistochemistry at the University of Padova, Italy on 13 spinal cord injury persons suffering up to 10 years of complete conus/cauda syndrome. Skin biopsies (n. 52) of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Skin biopsies fixed in formalin were embedded in paraffin at the Wilhelminenspital, Vienna, Austria. Histological sections of 5 µm thickness were collected and stained by Hematoxilin–Eosin [ 24 , 25 ] or by immuno-histochemistry to analyze CD1a, a biomarker of Langerhans cells [ 26 ], at the Section of Human Anatomy of the Neuroscience Department of Padova University, Italy.…”
Section: Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin biopsies fixed in formalin were embedded in paraffin at the Wilhelminenspital, Vienna, Austria. Histological sections of 5 µm thickness were collected and stained by Hematoxilin–Eosin [ 24 , 25 ] or by immuno-histochemistry to analyze CD1a, a biomarker of Langerhans cells [ 26 ], at the Section of Human Anatomy of the Neuroscience Department of Padova University, Italy.…”
Section: Diagnosticsmentioning
confidence: 99%
“…Here we add that the purpose-developed electrical fields delivered to ventral aspects of the thigh muscles by anatomically shaped large surface electrodes [ 22 ] produce clinically relevant recovery of the hamstring muscles [ 23 ] and of the thigh skin [ 24 , 25 , 26 ]. A believed drawback, co-activation of non-targeted muscles, is indeed responsible for a positive clinical result.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because we harvested muscle tissue through a skin biopsy, we had the opportunity to extend our analyses to skin. Excitingly, we found that the home-based Functional Electrical Stimulation-sustained improvements in muscle structure are extended to skin, whose thickness and flattening worsen in accordance with the extent of years of SCI, but are substantially recovered after 2-years of homebased Functional Electrical Stimulation [20][21][22]. the improvement of tissue trophism will be even more clinically relevant if patients add home-based functional electrical stimulation of Gluteal muscles to their training workout, as the Vienna Strategy for denervated degenerated muscles SCI strongly recommends.…”
Section: Advantages and Limitationsmentioning
confidence: 85%
“…Home-based Functional Electrical Stimulation-induced recovery of skin thickness from SCI-induced skin atrophy It is certainly worth noting, that we recently demonstrated, using skin biopsies harvested from the same series of RISE patients, that the skin also became atrophic and flattened (i.e., there were decreased numbers of papillae-like structures per mm of skin and a decreased interdigitation index of dermalepidermal junctions) after several years of SCI [30], but that these issues recovered from atrophy and flattening after 2-years of home-based Functional Electrical Stimulation applied to treat denervated degenerated muscles [20][21][22].…”
Section: Comparison Of Left Panels Ofmentioning
confidence: 97%
See 1 more Smart Citation